Financial Performance and Growth Prospects of PT Telkom Tbk: Empirical Ratio Based Analysis (2021–2024) - Purwandari, Dian; Lasmini, Lilis; Nasihin, Ihsan; Kartika, Erawati; Suprapti, Eny (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to evaluate the financial performance of PT Telekomunikasi Indonesia Tbk during the 2021–2024 period, particularly in relation to liquidity, solvency, activity, and profitability ratios. Methodology: The research adopts a quantitative approach with a causal research design, utilizing secondary data obtained from the company’s annual financial reports. Financial ratio analysis and linear regression analysis were employed to assess the influence of liquidity, solvency, activity, and profitability on overall financial performance. Results: The results indicate that the company’s liquidity experienced significant fluctuations and tended to be unstable, while solvency showed improvement, reflecting a stronger capital structure. However, asset utilization efficiency remained relatively low, limiting optimal performance. Profitability, measured by Return on Assets (ROA), was found to have the most significant influence on the company’s financial performance. Novelty: This study provides a comprehensive and integrated analysis of multiple financial ratios over a recent four-year period. Findings: Improving profitability and asset management efficiency is crucial to achieving stable and sustainable financial performance. Originality: The originality of this study lies in its focused empirical evaluation of a major Indonesian telecommunications company using recent financial data. Conclusions: PT Telekomunikasi Indonesia Tbk needs to strengthen liquidity stability and optimize asset utilization to support sustainable financial growth. Type of Paper: Empirical Research Paper.